Effects of silvicultural treatments in young Scots pine-dominated stands on the potential for early biofuel harvests - Ahnlund Ulvcrona, Kristina (2011)
The overall objective of the work underlying this thesis was to increase knowledge regarding growth of young Scots pine (Pinus sylvestris L.) - dominated mixed forests in northern Sweden and the potential for combining early biofuel harvest in such stands while leaving crop trees for future harvests. For this purpose, several studies were made. Biomass functions for the fractions stem (including bark), branches, foliage and whole trees were created for Scots pine, Norway spruce (Picea abies (L. Karst.), downy birch (Betula pubescens Ehrh.) and silver birch (Betula pendula Roth), based on measurements of the sampled trees in six young and dense stands (I). Growth and yield was studied for 8-11 years at four experimental sites (stand ages 17-20 years at start) in which density treatments (pre-commercial thinning, PCT, to 3 000 stems ha-1 and no-thinning; control, C) and fertilization treatments (N fertilization at 100 kg ha-1 every 6th year or annually: F1 and F2, respectively) had been applied alone and in two combinations (C+F1, C+F2 and PCT+F1). During the observation period total biomass yield was 58 - 79% higher (up to in total 100 ton ha-1 DW) in the dense, unthinned stands (>11 000 stems ha-1) than in the PCT stands. Fertilizing every year did not give significantly higher biomass production than the two fertilization applications. The 500 - 2 700 largest trees ha-1 showed significantly higher values of measured size parameters following treatment C+F2 compared to the unthinned control (C), but not to the PCT treatment, indicating that stand density only had minor effects on growth of the largest trees (II). When allocation patterns were analysed after six years, the only significant between-treatment differences found for Scots pine trees of various size classes were among the smallest trees (with a diameter at breast height, DBH, <5 cm). These trees had slenderer stems (lower DBH/height ratios) and lower relative proportions of branches and foliage in the dense, unthinned stands than in the PCT ...